2019
DOI: 10.1186/s13099-019-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between gut microbiota and type 1 diabetes? A systematic review

Abstract: Introduction Type 1 diabetes (T1D) is the second most common autoimmune disease among children. There is evidence suggesting that dysbiosis of some gut colonizing bacteria are associated with the pathogenesis of T1D. However, these studies are still controversial and a systematic review was conducted to evaluate the association between gut microbiota and T1D. Methods A systematic search was carried out in Medline (Via Pubmed) and Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 60 publications
(105 reference statements)
1
53
0
Order By: Relevance
“…A potential complication of diabetes mellitus is peripheral neuropathy with accompanying neuropathic pain and peripheral neuropathy is positively associated with insulin resistance (Han et al, 2015). Interestingly, patients with diabetes mellitus have a different gut microbiota composition and function compared to controls (Qin et al, 2012;Karlsson et al, 2013;Jamshidi et al, 2019). FMT may alter insulin resistance and thereby neuropathic pain.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…A potential complication of diabetes mellitus is peripheral neuropathy with accompanying neuropathic pain and peripheral neuropathy is positively associated with insulin resistance (Han et al, 2015). Interestingly, patients with diabetes mellitus have a different gut microbiota composition and function compared to controls (Qin et al, 2012;Karlsson et al, 2013;Jamshidi et al, 2019). FMT may alter insulin resistance and thereby neuropathic pain.…”
Section: Role Of the Gut Microbiota In Disease Symptoms And Pathogenesismentioning
confidence: 99%
“…Gut microbiota has an important role in the regulation of metabolism. Although causality between dysbiosis and T1D has not been proved yet in humans because long-term placebo-controlled trials are missing, literature data suggested a role of the gut microbiota in the disease development [27,28,104,105] and a recent published review concluded that the altered abundance of specific members or reduced diversity of gut microbiota was associated with the progression of T1D [106].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Research on environmental factors involved in the etiology of islet autoimmunity were focused on the role of viruses [20,21], early infant diet [22,23], childhood weight gain [24], vitamin D [25], gut microbiome [26][27][28], and environmental endocrine disrupting chemicals (EDCs) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Technologies are now available to better dissect the interplay between the host's microbiome and systemic immunity 4 ; at the same time, large cohorts of children at increased risk for T1D development have been monitored over time for gaining insight into the role of the microbiota in T1D prevention versus pathogenesis. 5 Recently, the TEDDY (The Environmental Determinants of Diabetes in the Young) study provided some evidence that early administration of probiotics (mostly, Lactobacillus and Bifidobacterium spp.) is associated with a reduced risk of islet autoimmunity.…”
Section: Introductionmentioning
confidence: 99%